Kebijakan Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) Dilihat dari Perspektif Hukum Internasional dan Politik Hukum dalam Pengendalian Penyebaran Covid-19 di Indonesia - Anis Khairiyah (Jurnal Hukum Lex Generalis, 2022)
The implementation of Restrictions on Community Activities (PPKM) is one of the government's policies in dealing with the Covid-19 Pandemic. The application of PPKM caused controversy both in terms of unfair application of sanctions and uneven social security that are normatively incompatible with the principles of national and international law. This research discusses the rules that apply in the establishment and application of PPKM from the perspective of international law and legal policy. The determination of the direction of legal political policy is seen through two indicators, namely the process of policy formation and policy implementation in the community. Democratic legal politics is the most ideal policy direction choice that must be chosen by the state so that PPKM policy should be in accordance with the direction of democratic legal political policy.